Rab3a-Bound CD63 Is Degraded and Rab3a-Free CD63 Is Incorporated into HIV-1 Particles - Kubo, Yoshinao; Masumoto, Hiroshi; Izumida, Mai; Kakoki, Katsura; Hayashi, Hideki; Matsuyama, Toshifumi (Frontiers in Microbiology, 2017)
CD63, a member of the tetraspanin family, is involved in virion production by human immunodeficiency virus type 1 (HIV-1), but its mechanism is unknown. In this study, we showed that a small GTP-binding protein, Rab3a, interacts with CD63. When Rab3a was exogenously expressed, the amounts of CD63 decreased in cells. The Rab3a-mediated reduction of CD63 was suppressed by lysosomal and proteasomal inhibitors. The amount of CD63 was increased by reducing the endogenous Rab3a level using a specific shRNA. These results indicate that Rab3a binds to CD63 to induce the degradation of CD63. Rab3a is thought to be involved in exocytosis, but we found that another function of Rab3a affects the fate of CD63 in lysosomes. CD63 interacted with Rab3a and was incorporated into HIV-1 particles. However, Rab3a was not detected in HIV-1 virions, thereby indicating that Rab3a-free CD63, but not Rab3a-bound CD63, is incorporated into HIV-1 particles. Overexpression or silencing of Rab3a moderately reduced HIV-1 virion formation. Overexpression of Rab3a decreased CD63 levels, but did not affect the incorporation of CD63 into HIV-1 particles. This study showed that Rab3a binds to CD63 to induce the degradation of CD63, and only Rab3a-free CD63 is incorporated into HIV-1 particles.